Identification Of Fungy Of Sweet Potato (Ipomoea Batatas) Tapai As Biology Learning Resources and It’s Effect toward Scientific Communication Skill Of The Xth Grade Student - G. Bramintha Pakartiar; Muzayyinah Muzayyinah; Meti Indrowati (Universitas Sebelas Maret, 2012)
The objectives of this research are (1) to identify kinds of fungi that can be found in sweet potato tapai, (2) to produce biology learning resources based on the research result of identification of fungi of sweet potato tapai (3) to find out the effect of the utilization of the research result based on identification of fungi of sweet potato tapai as a learning resources toward scientific communication skill of the Xth grade students of SMA Negeri 1 BoyolaliThis is a quasi - experimental research that use the true control group design (postest only). The independent variable in this research is biology learning resources whereas the dependent variable is scientific communication skill. The population of this research is entire student of the Xth grade of SMA Negeri 1 Boyolali Academic Year 2011/2012. The sample of this research consisted of two classes, control and experiment class. X2 class as a control group and X3 class as a experiment group. The sampling method using Cluster Random Sampling. The data collecting technique by using observation method. The test of the hypothesis in this research is using T – test method. From the research, it can be concluded (1) there are two kind of fungy that can be found in sweet potato tapai, i.e Aspergillus sp and Saccharomyces sp. Both of them have different characteristic. (2) An outline can be produced as biology learning resources based on the research result of identification of fungi of sweet potato tapai. (3) the utilization of the research result based on identification of fungi of sweet potato tapai as a learning resources has a positive impact towards the scientific communication skill of the Xth grade students Key Words: tapai fungy, biology learning resources, scientific communication skill